1995
DOI: 10.1016/0003-2670(94)00394-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characteristics of conductive carbon cement as matrix for chemically modified electrodes

Abstract: Electrochemical characteristics of conductive carbon cement as matrix for chemically modified electrodes Huang, X.; Pot, J.J.; Kok, W.T. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 63 publications
(16 reference statements)
1
20
0
1
Order By: Relevance
“…This is not what would be expected for a diffusion controlled process [16]. However, in previous studies with rotating-disk electrodes it was already found that the oxidation of glucose at the modified electrodes is at least partially controlled by reaction kinetics [15]. To eliminate the effect of flow rate on the peak dispersion, peak areas in FIA were also measured.…”
Section: Flow Injection Analysis and Liquid Chromatographymentioning
confidence: 94%
See 4 more Smart Citations
“…This is not what would be expected for a diffusion controlled process [16]. However, in previous studies with rotating-disk electrodes it was already found that the oxidation of glucose at the modified electrodes is at least partially controlled by reaction kinetics [15]. To eliminate the effect of flow rate on the peak dispersion, peak areas in FIA were also measured.…”
Section: Flow Injection Analysis and Liquid Chromatographymentioning
confidence: 94%
“…The Cu20/CCC working electrode (3 mm diameter) Was prepared as described previously [15]. For cyclic Voltammetry, a computerized Autolab electrochemical analyzer (ECO Chemie, Utrecht, The Netherlands) was Used.…”
Section: Experimental Instrumentalmentioning
confidence: 99%
See 3 more Smart Citations